An analysis of the relationship between additive manufacturing and circular economy - Tavares, Thais Moreira (Universidade Federal de São Carlos, 2022)
Additive Manufacturing (AM) is an important technology of Industry 4.0. It allows the fabrication of objects layer by layer in a continuous or incremental way. Circular Economy (CE) aims to improve resource efficiency in order to lead to a shift from the current linear model of receiving, transforming and disposing to a model where resources flow in a circular manner. Some early studies refer to Additive Manufacturing as a promise of sustainability and development of more circular material flows. However, there is still uncertainty about the impacts and benefits of Additive Manufacturing for circularity. From this context, this work aims firstly to understand the relationship between additive manufacturing and circular economy. To achieve this goal, a multi-method study was carried out to understand how AM is beneficial or challenging in a Circular Economy context. Second, it aims to collaborate in the implementation of AM strategies in an EC context. To coordinate the elaboration of the strategies, a second multi-method study was carried out, using a fuzzy DEMATEL method. This method was used to understand the interdependence relationships between the barriers raised in the first study. The study of these relationships is essential in the elaboration of strategies for implementing a more circular AM. The research contributes to practice and theory. In theory, it elaborates the state of the art of the intersection between the themes, evolving into a framework addressing benefits and barriers (validated by experts) that AM brings to CE. The study also contributes to practice by showing to organizations what developments and strategies need to take place to smooth the way for a circular AM.
Uma análise da relação entre manufatura aditiva e economia circular
Keywords: Manufatura aditiva; Impressão 3D; Economia circular; Sustentabilidade; Additive manufacturing; 3D printing; Circular economy; Sustainability; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO